Age‐related alterations in T‐lymphocytes modulate key pathways in prostate tumorigenesis1. Issue 8 (26th March 2013) - De Angulo, Alejandra; Faris, Robert; Cavazos, David; Jolly, Christopher; Daniel, Benajmin; deGraffenried, Linda
Abstract BACKGROUND The primary risk for prostate cancer is aging, often associated with inflammation. Evidence implicates progressive age‐related immune dysfunction with increased prostate cancer incidence and mortality. The aged T‐cell response is characterized by increased production of pro‐inflammatory cytokines, which could significantly contribute to prostate tumorigenesis through induction of key inflammation‐mediated pro‐survival factors. METHODS T‐cell function of the young (<6 month‐old) glycerol‐3‐phosphate acyltransferase‐1 (GPAT‐1) knock‐out mouse mimics many of the hallmarks observed in an aged (>22‐month‐old) mouse. Serum and splenic T‐lymphocytes from young GPAT‐1−/− (6 months) and aged wild type (22 months) mice were collected for in vitro studies, including a cytokine immunoarray for serum cytokine levels, luciferase assays for NF‐κB activation and Western blot analyses for protein expression. RESULTS The T‐cell cytokine profile of the GPAT‐1−/− mice mirrored that observed in aged wild type mice, including higher expression levels of IL‐17. Serum‐ and T‐cell‐derived factors induced NF‐κB activity in normal, non‐transformed and prostate cancer epithelial cells, correlating with re‐localization of NF‐κB and increased protein expression of downstream targets of NF‐κB. CONCLUSION The aging and aging‐mimic mice produced circulating factors that induce pro‐inflammatory pathways in prostate cells, most notably NF‐κB. These findings provide evidence that an aged T‐cell may directly contribute to the increased risk for prostate cancer in the elderly and establish that the GPAT‐1−/− model, which mimics many of the characteristics of an aged immune system, is a viable tool for investigating this novel area of cancer risk. Prostate 73: 855–864, 2013. © 2013 Wiley Periodicals, Inc.